Operculectomy Procedure as Treatment for Pericoronitis of the Lower Third Molar: A Case Reports - Liana Zulfa; Dahlia Nurzaleha; Hairunnisa A.Rakib (Lembaga Penelitian Universitas YARSI, 2025)
Introduction: The operculum surrounding the lower third molar can prompt plaque retention from accumulated food debris, and chewing trauma from opposing teeth can lead to pericoronitis. Pericoronitis typically occurs in the lower third molars. Case Report: A 17-year-old male patient and a 20-year-old female patient came with complaints of gums partially covering the crowns of their lower right tooth, which were painful when biting and interfered with eating. The patient had no systemic diseases, no drug or food allergies. Clinical and radiographic examinations revealed partial eruption of teeth 48. The operator decided to perform an operculectomy on tooth 48. Discussion: Operculectomy is the procedure to removal of the gum above the third molar. This is a surgical procedure to treat pericoronitis and prevent future recurrence. Conclusion: The operculectomy procedure using surgical blade was successful in this case because it is the gold standard and a conventional technique that can still be used for pericoronitis due to its ease of performance, affordability, and good healing process. The success of operculectomy treatment also depends on the patient's oral hygiene.